Post operative hearing status in canal wall down mastoidectomy with type III tympanoaplasty (Bangladesh Journal of Otorhinolaryngology, 2020)
Background: Canal wall down procedure may be with or without reconstruction such as tympanic membrane, ossicular chain or posterior canal wall reconstruction. To preserve and improvement of hearing, prevent discharge and recurrence, now a days canal wall down mastoidectomy with reconstruction such as type III tympanoplasty under magnification is a modern advancement in otology.Objectives: To find out hearing status before mastoidectomy and hearing status after canal wall down mastoidectomy with and without reconstruction.Methods: Prospectove study done on 3 tertiaty hospitals in Dhaka. Number of patients were 40 who underwent for modified radical mstoidectomy, 20 were with reconstruction and 20 without reconstruction (Type 3 Tympanoplasty)Results: hearing was deteriorated in most of the cases (60%) of MRM without tympanoplasty. Air Bone (AB) Gap Increased 3.65dB after CWD without reconstruction. Closer of AB gap (9.77 dB) occurred after CWD with reconstruction.Bangladesh J Otorhinolaryngol; October 2017; 23(2): 146-152